Elucidating the combinatorial effect of substrate stiffness and surface viscoelasticity on cellular phenotype - Chester, Daniel; Lee, Veronica; Wagner, Paul; Nordberg, Matthew; Fisher, Matthew B.; Brown, Ashley C. (Journal of biomedical materials research. Part A, 2022)
Cells maintain tensional homeostasis by monitoring the mechanics of their microenvironment. In order to understand this mechanotransduction phenomenon, hydrogel materials have been developed with either controllable linear elastic or viscoelastic properties. Native biological tissues, and biomaterials used for medical purposes, often have complex mechanical properties. However, due to the difficulty in completely decoupling the elastic and viscous components of hydrogel materials, the effect of complex composite materials on cellular responses has largely gone unreported. Here, we characterize a novel composite hydrogel system capable of decoupling and individually controlling both the bulk stiffness and surface viscoelasticity of the material by combining polyacrylamide (PA) gels with microgel thin films. By taking advantage of the high degree of control over stiffness offered by PA gels and viscoelasticity, in terms of surface loss tangent, of microgel thin films, it is possible to study the influence that bulk substrate stiffness and surface loss tangent have on complex fibroblast responses, including cellular and nuclear morphology and gene expression. This material system provides a facile method for investigating cellular responses to complex material mechanics with great precision and allows for a greater understanding of cellular mechanotransduction mechanisms than previously possible through current model material platforms. A novel composite hydrogel system capable of decoupling and individually controlling both the bulk stiffness and surface viscoelasticity of the material by combining polyacrylamide gels with microgel thin films is described. Fibroblast cellular and nuclear morphological changes and changes in gene expression in response to a wide range of these parameters are characterized.